Systematic theology - Thiselton, Anthony C. (William B. Eerdmans Publishing Company, 2015)
In this concise, one-volume systematic theology, celebrated scholar Anthony Thiselton covers the various Christian doctrines comprehensively with an eye to practical application for Christian discipleship. Written with students and busy ministers in mind, the book is readable and accessible, with its chapters organized into five fairly equal sections for teaching and learning convenience. Rather than setting out an abstract system, Thiselton explores theology as a living, organic whole. The book thus includes biblical foundations, historical thought, contemporary writers, and practical implications. Expertly incorporating biblical exegesis, philosophy, conceptual grammar, and hermeneutics, this volume is the most succinct multidisciplinary systematic theology available